Estágio Supervisionado: Programa de geração de emprego e renda em Araraquara no ano de 1997 - Kakinohama, Érika (Revista Segurança Urbana e Juventude, 2010)
The present work is part of the final report of a supervised training of the course of Public Administration from Araraquara University, UNESP, carried through in 1997. The focus of the training and the posterior reflection was the politics of job and income of the federal government and its applications in the municipal government. Here the duty municipal commission structure of job are detailed, as well as the programs and credit facilities of the Bank of Brazil. To the end, the challenge of overcoming unemployment and the precarious work is presented.